Illustrating memory: Clément Baloup’s Vietnamese Memories and the visual representation of the past - Gusain, Abhilasha; Jha, Smita (Penerbit Universiti Kebangsaan Malaysia, 2024)
The present study aims to highlight the role that Clément Baloup’s comics, Vietnamese Memories: Leaving Saigon (Volume 1) and Vietnamese Memories: Little Saigon (Volume 2), play in the creation of an alternate archive that validates the forgotten tales and the memories of a neglected past. These texts provide an alternate form of remembrance by materialising the past in the form of images. The two volumes present the unheard experiences of the Vietnamese diaspora that Baloup recorded during his travels to the different parts of France and the U.S. Such experiences bring to the forefront memories that are otherwise kept at the margins or suppressed by the dominant discourse. If not recorded, they will be lost forever. The counter-memory, thus, calls for a reassessment of the idea of a singular past that denies the marginalised memories. It claims representation and restoration in the cultural memory. As works of postmemory, these texts form a link between the past and the present through mediation and give memorability to unremembered accounts. The memories are illustrated, and hence, visual representation becomes important to the task of postmemory here.